Predisposing, Precipitating, Perpetuating, and Protective Factors Related to Distress in Family Members of Children with Cancer: A Systematic Review - Murawsky, Mackenzie (Université d'Ottawa / University of Ottawa, 2022)
Background: This systematic review aimed to identify factors related to psychological distress in family members of pediatric cancer patients on active treatment. Methods: Search strategies were entered into six academic databases. Randomized, nonrandomized, quantitative descriptive and mixed method studies, examining factors related to psychological distress in the population of study were included. Identified factors were coded as per the 4P’s of case formulation. Results: 59 studies were included. Parental factors identified: 24 predisposing factors; 12 precipitating factors; 35 perpetuating factors; and six protective factors. Sibling factors identified: five predisposing factors; one precipitating factor; 14 perpetuating factors; and two protective factors. A text-based, narrative synthesis and tabular summaries are presented. Discussion: Findings can support the: (1) recognition of distress exhibited in family members; and (2) the timing of interventions specific to the chronological manifestations of distress. Assessment of risk of bias was not done. Other: International Prospective Register for Systematic Reviews (PROSPERO) registration number CRD42018109802. No sources of funding to declare.
Keywords: Distress; Pediatric; Family members; Oncology